1989
DOI: 10.1016/0378-5955(89)90130-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of histamine as a hair-cell transmitter in the lateral line of Xenopus laevis

Abstract: The actions of histamine and histamine antagonists on afferent nerve activity were investigated in the lateral line of Xenopus laevis. Histamine (0.002-2.0 mM) had no effect on spontaneous activity or excitatory responses to water motion. In contrast, pyrilamine, an H1 receptor antagonist, suppressed spontaneous activity beginning at 0.01-0.05 mM. Below 0.3 mM the suppression was often preceded by a small excitatory response and responses to high (24-30 dB re threshold), but not low (0-18 dB) levels of water m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…This report suggested that histamine might have acted as a hair cell transmitter in frog, and the action site of H, antagonists that were used to treat vertigo and motion sickness was in such a peripheral location as the semicircular canal. In contrast, Bledsoe et al ( 1989) reported that histamine (0.002-2.0 mM) had no effect on the spontaneous activity of frog's ampullar nerve, whereas pyrilamine (0.0 l-0.05 mM), an H 1 antagonist, suppressed the spontaneous activity. Because histamine (2.0 mM) failed to block the actions of pyrilamine (0.1 mM), they concluded that the action of pyrilamine was nonspecific, possibly because of blockade of voltage-dependent sodium channels.…”
Section: Discussionmentioning
confidence: 86%
“…This report suggested that histamine might have acted as a hair cell transmitter in frog, and the action site of H, antagonists that were used to treat vertigo and motion sickness was in such a peripheral location as the semicircular canal. In contrast, Bledsoe et al ( 1989) reported that histamine (0.002-2.0 mM) had no effect on the spontaneous activity of frog's ampullar nerve, whereas pyrilamine (0.0 l-0.05 mM), an H 1 antagonist, suppressed the spontaneous activity. Because histamine (2.0 mM) failed to block the actions of pyrilamine (0.1 mM), they concluded that the action of pyrilamine was nonspecific, possibly because of blockade of voltage-dependent sodium channels.…”
Section: Discussionmentioning
confidence: 86%
“…Only two studies have studied the electrophysiological function of histamine in the mammalian inner ear [54,59]. Previous results obtained using the vestibular organ of frogs and lateral line of Xenopus laevis have suggested that histamine may act as a hair cell transmitter [69][70][71]. These studies provided evidence that histamine increases the afferent firing rate in nerves and that this afferent firing could be blocked by H 1 R and H 2 R antagonists.…”
Section: Electrophysiological Studies-the Role Of Histamine In the Tr...mentioning
confidence: 99%